Powder Characterization and Electrochemical Properties of LiNi0.5Mn1.5O4 Cathode Materials Produced by Large Spray Pyrolysis Using Flame Combustion - Shinsuke Akao; Motofumi Yamada; Takayuki Kodera; Kenichi Myoujin; Takashi Ogihara (Advances in Materials Science and Engineering)
LiNi0.5Mn1.5O4 cathode materials were produced by spray pyrolysis apparatus using the flame combustion. SEM revealed that as-prepared powders had spherical morphology with porous microstructure which had an average diameter of about 2 μm with broad size distribution. After the calcination, LiNi0.5Mn1.5O4 powders with polygonal morphology and narrow particle size distribution were obtained. XRD showed that LiNi0.5Mn1.5O4 was well crystallized after the calcination at 900°C. Rechargeable measurement of LiNi0.5Mn1.5O4 cathode showed that the long plateau was observed at 4.7 V in discharge curve of LiNi0.5Mn1.5O4 cathode and its discharge capacity was 145 mAh/g at 1 C. The capacity retention of LiNi0.5Mn1.5O4 cathode were 95% at 1 C after 100 cycles. The discharge capacity and capacity retention of LiNi0.5Mn1.5O4 cathode were 125 mAh/g and 88% at 20 C. LiNi0.5Mn1.5O4 cathode exhibited also stable cycle performance at 50∘C.